Post-Collisional Plio-Pleistocene Adakitic Volcanism in Centeral Iranian Volcanic Belt:Geochemical (Journal of Sciences, Islamic Republic of Iran)
In the Central IranianVolcanic Belt (CIVB), north-west of Shahre-Babak, in the area of Javazm, Dehaj and khabr, about 60 subvolcanic porphyritic dacitic to rhyodacitic domes (1-10 km2) are intruded into a variety of rock sequences from Mesozoic to Early Miocene in age. These rocks are a part of Dehaj-Sardoieh belt. The CIVB contains intrusive and extrusive rocks of Cretaceous-Quaternary age. Geochemical data indicate that the subalkalic dacitic to rhyodacitic rocks have an adakitic composition with Na2o/K2o (1.8-3.16), high Sr (584-1750 ppm), Mg # = (0.18-0.57) and low Y (7-10 ppm), low Yb (0.65-1.29 ppm), and low HREE. Fractionated REE patterns, (Ce/Yb)N = 10-27, absence of negative Eu anomal, low content of Y, Nb, Ti, and high Sr/Y (74-265) and (Ce/Yb)N ratios suggest that the source was probably hydrous garnet-amphibolite or amphibole-eclogite, possibly generated during subduction of the Neo-Tethyan oceanic slab beneath the Central Iran microplate.The adakitic volcanism was followed by eruption of alkaline magmatism in this area. Slab melting occurred after cessation of subduction, possibility from the collision. Transtensional tectonics accompanied by a locally extensional stress regime account for magma genesis and ascent.